Epidemiology and Prognosis of Progressive Pulmonary Fibrosis: A Literature Review - Ignacio Español Montero; Fernanda Hernandez-Gonzalez; Jacobo Sellares (Pulmonary Therapy)
Abstract The spectrum of interstitial lung diseases (ILDs) includes a wide range of clinical entities with variable disease courses and prognoses. Several ILDs other than idiopathic pulmonary fibrosis (IPF) may exhibit a progressive fibrotic phenotype, with diverse clinical presentation, histopathological and radiological patterns, as well as varying rates of disease progression and uncertain epidemiology, but with a similar prognosis of untreated idiopathic pulmonary fibrosis with irreversible lung function deterioration, substantial worsening of quality of life and early mortality. The recently defined term “progressive pulmonary fibrosis” (PPF) stands as an opportunity to better classify patients with progressive fibrotic disease and other IPF, irrespective of the underlying ILD. The definition of disease progression, including factors such as pulmonary function test decline, radiological progression, and symptomatic worsening, was not adopted until recently, thus significantly impacting the certainty of current estimates of incidence and prevalence and prognostic outcomes. Understanding disease progression in the broad spectrum of potentially progressive ILDs is key for developing standardized management algorithms irrespective of the ILD diagnosis. Current evidence points towards the potential beneficial effect of antifibrotic drugs in lung function decline and overall outcomes in several non-IPF progressive ILDs showing progression despite optimal management.